The Evaluation Of Efficiency Of Different Types Of Fuel For Proton Car - Samsudin, Adam; Rodzi, Muhammad Amirun Mukmin; Zainal Abidin, Amar Faiz; Hasim, Nur Aiman Hanis; Azmi, Ezzatul Farhain (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
This paper presents the overall view of the method for obtaining information on the use of fuels on the Proton Saga FLX 1.3 car. Proton Saga FLX 1.3 is used because the car is a car that is often used by Malaysians. This is based on its low price and has an ergonomic that is fit for Malaysians. To see which fuels is more effective on the Proton Saga FLX 1.3 car. This study conducted tests on three different roads. This is to identify whether friction on each road or additional force when mounting a hill contributes to the use of fuels. In addition, this study was repeated three times for more accurate data. The roads used are highways, domestic and hilly roads. The fuels used in this study is RON 95 and RON 97 fuels. This is because the fuels are the ideal fuel for Proton Saga cars. In addition, this fuel is often found in petrol stations in Malaysia. So it can help people in choosing the best fuel on their Proton Saga car.